Tinea Corporis pada Kondisi Pascabencana Banjir: Peran Kelembapan, Kebersihan Personal, dan Paparan Lingkungan - Ahmad Azhari; Cut Khairunnisa (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Tinea corporis is the most common form of dermatophytosis found in Asia, accounting for approximately 35.4 per cent of cases. Tinea can be transmitted both directly and indirectly. In order to infect a host, dermatophytes must be able to adhere to, penetrate the tissue, and survive under various host conditions, such as temperature and environment. Mrs J attended the outpatient clinic at the Kuta Makmur Community Health Centre complaining of itching on her body, particularly in the groin area, which had started two months previously and had worsened over the past four days. In the itchy areas, a red border was observed with a central area that was healing. Initially, the patches were merely itchy; two weeks later, the patient noticed patches appearing on her elbows, which subsequently spread to her shoulders and groin, becoming thicker and accompanied by scaling. The itching comes and goes and worsens when the patient sweats. To relieve the itching, the patient frequently scratches the affected areas but does not cause any breaks in the skin. These symptoms are disrupting the patient’s daily activities. On anogenital physical examination, a reddish patch measuring 8–10 cm was observed, with central healing and raised edges accompanied by fine scales.